A modified multiple cross displacement amplification linked with a gold nanoparticle biosensor for the detection of Epstein-Barr virus in clinical applications - Zeng, Xiaoyan; Yang, Xinggui; Yang, Ludi; Yi, Xu; Chen, Xu; Huang, Junfei; Wang, Yu; Li, Shijun (Frontiers in Microbiology, 2023)
Epstein-Barr virus (EBV), a double-stranded DNA virus belonging to the family Herpesviridae, infects more than 95% of healthy adults by attacking the host immune system. Here, a novel detection protocol, utilizing the modified multiple cross displacement amplification (MCDA) technique combined with a gold nanoparticles-based lateral flow biosensors (AuNPs-LFB), was devised and developed to detect EBV infection (termed EBV-MCDA-LFB assay). Eight MCDA primers targeting the EBNA-LP gene were designed, including CP1* primers modified with 6-carboxyfluorescein (FAM) and D1* primers modified with biotin. Then, nucleic acid templates extracted from various pathogens and whole blood samples were used to optimize and evaluate the EBV-MCDA-LFB assay. As a result, the lowest concentration of EBNA-plasmids, which can be detected by MCDA-LFB assay with an optimal reaction condition of 67℃ for 30 min, was 10 copies/reaction. Here, the MCDA-LFB assay can detect all EBV pathogens used in the study, and no cross-reactions with non-EBV organisms were observed. Meanwhile, the entire detection workflow of the EBV-MCDA-LFB assay for whole blood samples, including DNA template preparation (25 min), EBV-MCDA amplification (30 min), and AuNPs-LFB-mediated validation (2-5 min), can be completed within 1 h. Taken together, the EBV-MCDA-LFB assay established in the current study is a rapid, simplified, sensitive, specific, and easy-to-obtain technique that can be used as a screening or diagnostic tool for EBV infection in clinical applications, especially in resource-poor regions.